CUKA AREN (Arenga pinnata): KAJIAN PEMANFAATAN OLEH INDIGENOUS PEOPLE KAMPUNG ADAT KUTA BERDASARKAN FLOK KNOWLEGDE - Reza Fauzi Dwisandi; Diana Hernawati; Egi Nuryadin (Florea : Jurnal Biologi dan Pembelajarannya, 2021)
Palm vinegar is one of the processed products from a type of plant from the Arecaceae family, namely Arenga pinnata. Arenga vinegar is used by the people of the Kuta traditional village as a traditional medicine to treat a disease or prevent disease, this is based on folk knowledge, experience and ancestral traditions passed down from generation to generation in using plants as medicine. However, their utilization practices have not been published, identified and documented. Therefore, this study aims to describe the stages of making arenga vinegar and the practice of using it as a traditional medicine in Kuta Traditional Village. This research was conducted in Kuta Traditional Village, Tambak Sari District, Karangpaninggal Village, Ciamis Regency, in January-February 2021. This research is qualitative research study using the phenomenological method, the data collection technique used in this study are passive participation and active participation observation, semi-structured interviews with 4 people, namely 3 men and 1 woman, and document studies were carried out. The results showed that the arenga vinegar making stages in Kuta Traditional Village includes the process of lodong sterilizer, tapping arenga juice, filtering arenga juice, storing and fermenting arenga juice. As for its use, arenga vinegar is believed to be a traditional medicine such as types of fever, aches, liver, diabetes, stomach acid and external wounds.